WONDER OPENS THE HEART: POPE FRANCIS AND LISA SIDERIS ON NATURE, ENCOUNTER, AND WONDER: with Holmes Rolston, III, "Lame Science? Blind Religion?"; Sarah E. Fredericks, "Reacting to Consecrating Science: What Might Amateurs Do?"; Donovan O. Schaefer, "Mere Science: Mapping the Land Bridge between Emotion, Politics, and Ethics"; Courtney O'Dell‐Chaib, "The Shape of This Wonder? Consecrated Science and New Cosmology Affects"; Colin McGuigan, "Wonder Opens the Heart: Pope Francis and Lisa Sideris on Nature, Encounter, and Wonder"; Mary Evelyn Tucker, "Journey of the Universe: Weaving Science with the Humanities"; and Lisa H. Sideris, "Wonder Sustained: A Reply to Critics.". Issue 2 (14th May 2019) - McGuigan, Colin
Abstract: This article argues that Pope Francis's invocations of wonder can speak to and at times challenge Lisa Sideris's recent contributions to the interdisciplinary discussion of wonder, science, and religion. Although the importance of wonder to Pope Francis's 2015 environmental encyclical Laudato si' is acknowledged, it has not been widely recognized that wonder is implicated in and forms connections between multiple concepts and postures acknowledged as defining marks of Francis's papacy: coming out of oneself, encountering others, going to the margins; aversion to doctrinal rigidity; compassion, mercy, tenderness, and humility; to name a few. These defining concepts and stances resonate strongly with certain views on wonder, ethics, and ecology recently articulated by Lisa Sideris. In Francis, however, one finds a more affirming treatment of science‐based wonder and a response to Sideris's criticism of theistic wonder.